Carmelitas descalzas en San Sebastián. Últimas décadas: 1975-2020. Dos perspectivas - Rodriguez-San Pedro Bezares, Luis E.; Ocio Madina, Maite (Boletín de la Real Sociedad Bascongada de Amigos del País, 2023)
It describes the last decades of the convent life of the Carmelite Nuns of San Sebastian, between 1975 and the year 2020, the date of the convent’s closure. Two perspectives are offered: an internal one, from the point of view of the community of nuns, and an external one from historical perspectives. An appendix of notes and photographs is added.